Husbands’ Knowledge as a Determinant of IUD Contraceptive Selection in Pangalengan, 2025 - Aba, Matheus; Liska, Cici; Soffa, Maya (Rifa'Institute, 2026)
Introduction: Intrauterine device contraception offers superior efficacy and long-term benefits, yet utilization rates remain low in Indonesia. Husbands' knowledge significantly influences household contraceptive decisions within patriarchal family structures. Objective: This study examined the relationship between husbands' knowledge and intrauterine device contraceptive selection among couples of reproductive age in Pangalengan Subdistrict, Bandung Regency. Method: A descriptive correlational cross-sectional study was conducted with 86 husbands selected through purposive random sampling. Data collection utilized validated questionnaires assessing knowledge and contraceptive selection patterns. Chi-square analysis examined variable relationships. Result and Discussion: The majority of husbands (55.8%) demonstrated poor knowledge regarding intrauterine device contraception. Only 22.1% of couples selected intrauterine device methods. Statistical analysis confirmed significant relationships between husbands' knowledge and intrauterine device selection (p-value = 0.001). Among husbands with good knowledge, 63.6% selected intrauterine device contraception compared to 10.4% among those with poor knowledge, demonstrating clear dose-response patterns. Conclusion: Husbands' knowledge significantly influences intrauterine device contraceptive selection. Targeted educational interventions incorporating male engagement strategies are essential to enhance long-acting reversible contraceptive uptake and improve reproductive health outcomes.